2015
DOI: 10.5152/balkanmedj.2015.151223
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Association of Immune Thrombocytopenia in Adults

Abstract: Background:Immune thrombocytopenia (ITP) is an autoimmune disorder. It is characterized by thrombocytopenia due to thrombocyte destruction mediated by autoantibodies; however, cytotoxic and defective regulatory T-lymphocytes play an important role in its pathogenesis. While childhood ITP is usually acute, self-limiting and generally seasonal in nature, ITP in adults is usually chronic; its relation with seasons has not been studied. Aims: We investigated whether months and/or seasons have triggering roles in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
(37 reference statements)
2
6
1
Order By: Relevance
“…ITP was the second most common disorder found in our cohort, with female preponderance and most cases being found in southwest monsoon period and peak was found in the month of April. This is similar to international studies, which showed most cases of primary ITP were diagnosed in spring 2,20 . With respect to months, the majority of cases occurred in May 2 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…ITP was the second most common disorder found in our cohort, with female preponderance and most cases being found in southwest monsoon period and peak was found in the month of April. This is similar to international studies, which showed most cases of primary ITP were diagnosed in spring 2,20 . With respect to months, the majority of cases occurred in May 2 .…”
Section: Discussionsupporting
confidence: 90%
“…A childhood study of seasonality in leukemia has shown peaks of diagnosis in summer season, while in a study on adults, higher incidence was observed in winter season 9,10 . Another study has reported significantly higher incidence of primary ITP in spring season 2 …”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Atopic disorders such as allergic conjunctivitis, asthma, allergic rhinitis can occur in other diseases such as Immune thrombocytopenic purpura (ITP). ITP is one of the most common causes of thrombocytopenia and is a syndrome that causes platelet dysfunction 12 . Antiplatelet antibodies secreted by autoreactive B lymphocytes destroy platelets in the reticuloendothelial system, especially the spleen by binding to platelet antigens, which is described as the major immunological defect in ITP 13 .…”
mentioning
confidence: 99%